Aggressive spectators in sporting milieus: a test of situational action theory - Kabiri, Saeed (Global crime, 2023)
Violence among spectators in sports is a global phenomenon posing hazards for players, match officials, and other participants. Despite its widespread prevalence, scant criminological research has investigated the matter. To fill this void, this study examines the predictive efficacy of key theoretical constructs derived from Situational Action Theory on aggressive behaviour among a sample of 384 soccer spectators in Iran. Results reveal that crime propensity, criminogenic exposure, action alternatives, and choice have direct effects on spectator engagement in violent behaviour. Furthermore, results demonstrate that crime propensity and criminogenic exposure (propensity*exposure) and action alternatives and choice (action alternatives*choice) interact to increase violence among sport spectators in a manner consistent with the theory. Theoretical and policy implications are discussed.